Uncertainty Modeling for Participation of Electric Vehicles in Collaborative Energy Consumption - Hashemipour, Naser; Aghaei, Jamshid; Del Granado, Pedro Crespo; Kavousi-Fard, Abdollah; Niknam, Taher; Shafie-khah, Miadreza; Catalao, Joao P.S. (IEEE, 2022)
This paper proposes an accurate and efficient probabilistic method for modeling the nonlinear and complex uncertainty effects and mainly focuses on the Electric Vehicle (EV) uncertainty in Peer-to-Peer (P2P) trading. The proposed method captures the uncertainty of the input parameters with a low computational burden and regardless of the probability density function (PDF) shape. To this end, for each uncertain parameter, multitude of random vectors with the specification of corresponding uncertain parameters are generated and a fuzzy membership function is then assigned to each vector. Since the most probable samples occur repeatedly, they are recognized by the superposition of the generated fuzzy membership functions. The simulation results on various case studies indicate the high accuracy of the proposed method in comparison with Monte-Carlo simulation (MCs), Unscented Transformation (UT), and Point Estimate Method (PEM). It also scales down the computational burden compared to MCs. Also, a real-world case study is employed to examine the ability of the method in capturing the uncertainty of EVs’ arrival and departure time. The studies on this case reveal that involving EVs in P2P trading augments the amount of energy traded within the prosumers.
Keywords: EV Uncertainty; P2P trading; Uncertainty Modeling; Vehicle to Home; fi=Sähkötekniikka|en=Electrical Engineering|